A comparative study of coagulation profile and platelet indices at term in pre-eclamptic, eclamptic and normal pregnancy along with fetomaternal outcome - Indora, Prachika; Gandhi, Sudha; Agarwal, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Hypertensive disorders of pregnancy is reported to cause about 60-80% of maternal deaths. Platelet indices are biomarkers of platelet activation. Among these platelet indices, mean platelet volume (MPV), and platelet distribution width (PDW), platelet large cell ratio (PLCR) is a group of platelet parameters. When platelets are activated, they become larger in size which causes increased platelet indices such as MPV, PDW and PLCR. So, platelet indices can give an idea of platelet activation. A comparative study of coagulation profile and platelet indices at term in pre-eclamptic, eclamptic and normal pregnancy along with fetomaternal outcome. Methods: This study was carried out in department of obstetrics and gynaecology in collaboration with department of pathology, Rabindranath Tagore Medical College (RNTMC), Udaipur. Cases were selected by systematic random sampling. Bleeding time (BT), clotting time (CT), prothrombin time (PT), mean platelet volume (MPV), platelet distribution width (PDW), and activated partial thromboplastin time (aPTT) to analyse hypertensive disorders in pregnancy (HDP) during the period January 2021 to December 2021. Results: Significant difference was seen in bleeding time (seconds), prothrombin time (seconds), aPTT (seconds) between normal pregnancy as compared to pre-eclampsia and eclampsia. (p value <0.05). Patients’ admission in neonatal intensive care unit (NICU) was significantly higher in eclampsia (p<0.0001) and pre-eclampsia (p<0.0001) as compared to normal pregnancy (66.67%, 43.24% versus 2% respectively). Conclusions: We conclude that coagulation profile like (BT, CT, PT, and aPTT), platelet counts along with platelet indices- MPV, PDW are useful markers, which were significantly raised in patients with preeclampsia and eclampsia. Platelet indices along with coagulation profile emerges as an important, simple, cost effective and effortless tool for predicting severity of pregnancy induced hypertension (PIH).